Conjunto de datos: Vespula vulgaris population growth in Patagonia - Masciocchi, Maite (2021)
Cobertura espacial: San Carlos de Bariloche, Rio Negro, Argentina (41o 8´ 22´´ S and 71o 2´ 7´´ W). Cobertura temporal: from 26 of February of 2021, for 13 weeks.